Academic burnout viewed from working students’ self-management in Madiun city - Prahanasti Alsandi; Marcella Mariska Aryono (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
The purpose of this study was to determine the correlation between academic burnout and self-management of students who both study and work in the city of Madiun. Respondents in this study were 96 working students. Sampling was selected by purposive sampling method. This study used a quantitative method with data collection measuring tools of academic burnout scale and self-management scale. The data collected were tested using Pearson Product Moment. The test resulted in a coefficient value of -0.745 with a significance of 0.000, meaning that there is a correlation between academic burnout and self-management of students who are currently working in Madiun City